Using home maintenance and repairs to smooth variable earnings - Joseph Gyourko; Joseph Tracy (Federal Reserve Bank of New York, 2003)
Recent research indicates that the marked increase in U.S. income inequality over the last twenty-five years has not been matched by a similar increase in consumption inequality. This paper examines the role of saving/dissaving in a house as a vehicle for consumption smoothing. Data from the American Housing Survey show that expenditures on home maintenance and repairs are economically significant, amounting to roughly 1,750 per household each year. This figure is comparable to the labor literature estimates that put households' average annual transitory income variance at about 2,200. Our calculations show a significant elasticity of maintenance and repair expenditures to transitory income shocks. The elasticities are higher for less well educated households, which are more likely to be liquidity constrained than their better educated counterparts.
Keywords: D12; E21; R21; 330; Sparen; Gesamtwirtschaftlicher Konsum; Gebäudeinstandhaltung; Elastizität; Haushaltseinkommen; Schock; USA